Как вы упростите \((-x^2 +9x -2) -(9x^2- 4x+ 4\))?

0
0

Как вы упростите \((-x^2 +9x -2) -(9x^2- 4x+ 4\))?

0
0

\[-10x^2 + 13x — 6\] Объяснение:

Все, что вам нужно сделать, это в значительной степени вычесть различные переменные питания \[(Ex. x^3, x^2, x)\] так … \[-x^2 — 9x^2 = -10x^2\] \[9x — (-4x) = 13x\] \[-2 — 4 = -6\] Ответ: \[-10x^2 + 13x -6\]

0
0

\[(x^2+9x-2)-(9x^2-4x+4)=-8x^2+13x-6\] Объяснение: \[(x^2+9x-2)-(9x^2-4x+4)\] \[=x^2+9x-2-9x^2+4x-4\] \[=x^2-9x^2+9x+4x-2-4\] \[(1-9)x^2+(9+4)x-(2+4)\] \[-8x^2+13x-6\]

Показано 2 результатов